Derecho fundamental al secreto e inviolabilidad de las comunicaciones: análisis comparado de su sentido y contenido - Velásquez Meléndez, Raffo (Pontificia Universidad Católica del Perú, 2025)
The author conducts a thorough analysis of the fundamental right to the secrecy and inviolability of communications from a jurisprudential, doctrinal, and legislative perspective, taking into account the challenges posed by technological advancements. The author asserts that this constitutional right ensures the protection of communications against arbitrary interferences, particularly in a context where the widespread use of the internet and mobile devices has heightened the risk of privacy infringements. Furthermore, the author contends that any restriction on this right is only permissible in exceptional circumstances, subject to prior judicial authorization and strict adherence to the principle of legality. In substantiating the study, the author draws upon constitutional provisions, international human rights instruments, and comparative law, all of which recognize this right as a cornerstone of the rule of law. Moreover, it is underscored that any limitation on this fundamental guarantee must be expressly prescribed by law, adhere to the principles of necessity and proportionality, and be subject to rigorous judicial scrutiny.

El autor realiza un análisis exhaustivo del derecho fundamental al secreto y la inviolabilidad de las comunicaciones desde una perspectiva jurisprudencial, doctrinal y legislativa, atendiendo a los desafíos que plantea el desarrollo tecnológico. Asimismo, considera que este derecho constitucional garantiza la protección de las comunicaciones frente a injerencias arbitrarias, especialmente en un contexto donde el uso de internet y dispositivos móviles ha incrementado el riesgo de vulneraciones a la privacidad; y que su restricción solo es admisible en supuestos excepcionales, bajo autorización judicial previa y con estricta observancia del principio de legalidad. Para fundamentar su estudio, el autor se apoya en las disposiciones constitucionales, los instrumentos internacionales de derechos humanos y el Derecho Comparado, todos ellos coincidentes en reconocer este derecho como un pilar esencial del Estado de Derecho. Asimismo, se destaca que cualquier restricción a esta garantía debe estar expresamente prevista en la ley, cumplir con los principios de necesidad y proporcionalidad, y estar sujeta a un control jurisdiccional efectivo.
Fundamental right to secrecy and inviolability of communications: comparative analysis of its meaning and content
Keywords: Right to privacy; Right to respect for private life; Elements of the communication process; Confidentiality of communications; Reasonable expectation of privacy; Derecho a la intimidad; Derecho a la privacidad; Elementos del proceso de comunicación; Secreto de las comunicaciones; Expectativa razonable de privacidad; https://purl.org/pe-repo/ocde/ford#5.05.01